Interaction Studies of Chlorpheniramine Maleate in Mono and Dihydric Alcohols by Density, Viscosity, and HPLC Methods - Zainab Khan; Summyia Masood; Nighat Shafi; Rafia Azmat; Salman Khurshid; Samreen Begum (Indonesian Journal of Chemistry, 2022)
The examination of a drug in water and other aqueous systems gives insight into the chemistry of biological systems. This work aims to study the physico-chemical properties of chlorpheniramine maleate (drug) in water and aq-MeOH/EG (mono/dihydric alcohols) systems at different temperatures by using different techniques. Densities and viscosities of chlorpheniramine maleate in water and also in MeOH/EG aqueous solutions have been measured over a temperature range of 298.15 to 318.15 K. Number of several parameters, i.e., apparent molar volume (ϕv), partial molar volume (ϕvo), Hepler’s constant (∂CΡ/∂Ρ)T, Falkenhagen coefficient (A), and Jones-Dole coefficient (B) have been calculated by using experimentally measured density and viscosity values. The mentioned calculated parameters were found to be valuable in perceiving drug-drug and drug-solvent interactions. Moreover, one of the liquid chromatographic techniques such as RP-HPLC has also been performed, and the outcomes supported the conclusion procured from the volumetric and viscometric studies. Drug interactions help to understand their behavior in different solvent systems during drug development.